Representations of gender in annual reports in the real estate industry in Sweden. Issue 1 (15th February 2016) - Staffansson Pauli, Karin Maria
Abstract : Purpose: – The purpose of this paper is to clarify how annual reports of public housing and commercial real estate companies contribute in "doing gender" of the real estate industry in Sweden. How the issue of gender is dealt with in photographs, in two different types of organizations, with different corporate and business strategies, is important as they play a significant role in constructing the industry itself. Are there any differences in how they perceive gender, and what constitutes gender of the industry? Design/methodology/approach: – Analysis of photographs in annual reports, 14 public housing companies and eight commercial real estate companies, in the year of 2011. Findings: – The paper provides empirical insights about how "gender is done" in annual reports, men alone are shown more often as employees and both women and men are portrayed in stereotypical positions. Women are depicted more often as young and also presented in "token positions". Research limitations/implications: – Because of the chosen research approach, in studying only one year, a longitudinal study would be recommended for future studies. Practical implications: – The paper includes implications for the development of gender symbols and images representing the industry, in how gender is done in public situations as in annual reports. This is not only important for the industry itself but also to stakeholders involved with the industry. Originality/value: – This paper fulfils an identified need to study how photographs shown in annual reports reveal gender structure.